Immunohistochemical study of the distribution of serotonin in the gastrointestinal tract of the porcupines (Hystrix cristata) - Timurkaan, S; Karan, M; Aydin, A (Ecole Nationale Veterinaire Toulouse, 2005)
The occurence and distribution of serotonin in the endocrine cells of gastrointestinal tract of the porcupine (Hystrix cristata), were investigated using immunohistochemical method. Serotonin immunoreactive cells were located in the gastric glands and in the intestinal epithelium with variable frequencies. They were spherical or spindle-shaped. Serotonin immunoreactive cells were detected in almost all regions of the gastrointestinal tract and they showed highest frequency in the stomach and colon.
Keywords: immunohistochemistry; serotonin; endocrine cells; gastrointestinal tract; porcupine